Evaluasi Irigasi Berbasis Teknologi Di Sektor Pertanian - Zebua, Siska Natalia; Dohona, Nurul Hamidah; Waruwu, Inca Paskahlia (CV. SINAR HOWUHOWU, 2024)
The evaluation of technology-based irrigation in the agricultural sector aims to assess the effectiveness and impact of modern irrigation technologies in improving water use efficiency, crop productivity, and environmental sustainability. This study examines the application of automated irrigation systems based on soil moisture sensors and drip irrigation technology in several agricultural areas. The research findings show that the use of sensor-based irrigation technology can reduce water usage by 35-40%, compared to conventional irrigation methods, which tend to be more wasteful. In addition, this technology increases crop productivity by approximately 20-25% due to more efficient and timely water distribution. Operational costs are also reduced, particularly in terms of water consumption and labor. Another positive impact is the contribution of irrigation technology to environmental conservation, by reducing water waste and preventing damage to agricultural ecosystems. Although the higher initial investment cost poses a challenge, long-term results indicate that sensor-based irrigation technology provides significant benefits for the agricultural sector, both economically and environmentally. This study recommends the wider adoption of irrigation technologies, supported by policies that facilitate access and training for farmers.